A case of lipedematous alopecia - Jiameng ZHU; Ling HUANG; Canmei LI; Jing XU; Changwen NI; Rubin YANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
A case of lipedematous scalp complicated by lipedematous alopecia is reported. A 44-year-old woman presented with a 5-year history of gradual swelling and diffuse hair thinning and alopecia. Dermatological examination showed a fusiform area with thinning hair, sized 9 cm×18 cm, and some residual broken hair <2 cm, on the top of the scalp. The skin on the hair loss area was yellowish brown and slightly elevated, but significantly thickened, with soft and spongy feeling. Hair pulling test was negative. Dermoscopic examination showed no inflammation on the scalp, no exclamation marker hair, no black dot sign, no yellow dot sign, and no cluster hair. No rash was found on the patient's face and other sites of the skin. MRI of the head revealed irregular thickening of the subcutaneous fat layer on the scalp. The biopsy revealed reduced number of hair follicles, replacement of hair follicles by proliferative fibrous tissue, and perifollicular infiltrate of lymphocytes. The final diagnosis was lipedematous scalp complicated with lipedematous alopecia. The patient and his family members refused treatment. After followed up for more than half a year, the condition remained unchanged.